Impacts of chemical enhancers on skin permeation and deposition of terbinafine. (August 2014) - Erdal, Meryem Sedef; Peköz, Ayca Yıldız; Aksu, Buket; Araman, Ahmet
Abstract Context/Objective: The addition of chemical enhancers into formulations is the most commonly employed approach to overcome the skin barrier. The objective of this work was to evaluate the effect of vehicle and chemical enhancers on the skin permeation and accumulation of terbinafine, an allylamine antifungal drug. Methods: Terbinafine (1% w/w) was formulated as a Carbopol 934 P gel formulation in presence and absence of three chemical enhancers, nerolidol, dl-limonene and urea. Terbinafine distribution and deposition in stratum corneum (SC) and skin following 8-h ex vivo permeation study was determined using a sequential tape stripping procedure. The conformational order of SC lipids was investigated by ATR-FTIR spectroscopy. Results and discussion: Nerolidol containing gel formulation produced significantly higher enhancement in terbinafine permeation through skin and its skin accumulation was increased. ATR-FTIR results showed enhancer induced lipid bilayer disruption in SC. Urea resulted in enhanced permeation of terbinafine across the skin and a balanced distribution to the SC was achieved. But, dl-limonene could not minimize the accumulation of terbinafine in the upper SC. Conclusion: Nerolidol dramatically improved the skin permeation and deposition of terbinafine in the skin that might help to optimize targeting of the drug to the epidermal sites as required for both of superficial and deep cutaneous fungal infections.